Personality Traits and Cognitive Emotion Regulation Strategies as Predictors of Depression, Anxiety, and Stress - Simić, Tijana LJ.; Milutinović, Kristina M.; Popović, Emilija U.; Pavićević, Miljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The aim of this study was to examine the contribution of cognitive emotion regulation strategies in predicting depression, anxiety, and stress in young adults, beyond the basic personality dimensions. The sample consisted of 173 participants aged between 18 and 40 years. The Big Five Inventory (BFI), the Depression, Anxiety, and Stress Scale (DASS-21), and the Cognitive Emotion Regulation Questionnaire (CERQ) were used. Data were analyzed using hierarchical regression analyses. The results indicate that neuroticism was the strongest and most consistent predictor of depression, anxiety, and stress. Extraversion and conscientiousness emerged as significant negative predictors of depression, while conscientiousness also showed a protective role in relation to anxiety. Agreeableness was negatively associated with stress, whereas openness to experience showed a positive contribution to stress prediction. Regarding cognitive emotion regulation strategies, self-blame, catastrophizing, and blaming others were associated with higher levels of depressive symptoms, while self-blame also emerged as a significant predictor of anxiety and stress. In contrast, positive refocusing demonstrated a protective effect against depression. These findings highlight the importance of jointly considering stable personality traits and cognitive emotion regulation strategies in understanding emotional distress and emphasize their relevance for prevention and the development of targeted psychological interventions.
Keywords: personality traits; cognitive emotion regulation; depression; anxiety; stress